2021
DOI: 10.1038/s42004-021-00548-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal scales of variability for indoor air constituents

Abstract: Historically air constituents have been assumed to be well mixed in indoor environments, with single point measurements and box modeling representing a room or a house. Here we demonstrate that this fundamental assumption needs to be revisited through advanced model simulations and extensive measurements of bleach cleaning. We show that inorganic chlorinated products, such as hypochlorous acid and chloramines generated via multiphase reactions, exhibit spatial and vertical concentration gradients in a room, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
(52 reference statements)
1
29
0
Order By: Relevance
“…However, for the 10% flow condition and mixed‐mode ventilation, the zero‐dimension well‐mixed approach produces quite similar results in terms of both the average risk (and thus R event ) and the probability distribution of secondary cases. The parameters under which well‐mixed approaches are most defensible requires further evaluation, using CFD and possibly field investigations (e.g., tracer tests) to inform such generalizations; nonetheless, it is clear that well‐mixed models can perform very well in scenarios characterized by low air exchange rates where the flow patterns are not able to provide a proper particle removal from the breathing zone of the exposed subject: this is also typical of other larger indoor environments, such as naturally‐ventilated buildings, 32 where well‐mixed models were shown to predict the attack rates of documented SARS‐CoV‐2 outbreaks. 21 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for the 10% flow condition and mixed‐mode ventilation, the zero‐dimension well‐mixed approach produces quite similar results in terms of both the average risk (and thus R event ) and the probability distribution of secondary cases. The parameters under which well‐mixed approaches are most defensible requires further evaluation, using CFD and possibly field investigations (e.g., tracer tests) to inform such generalizations; nonetheless, it is clear that well‐mixed models can perform very well in scenarios characterized by low air exchange rates where the flow patterns are not able to provide a proper particle removal from the breathing zone of the exposed subject: this is also typical of other larger indoor environments, such as naturally‐ventilated buildings, 32 where well‐mixed models were shown to predict the attack rates of documented SARS‐CoV‐2 outbreaks. 21 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…However, for the 10% flow condition and mixed-mode ventilation, the zero-dimension well-mixed approach produces quite similar results in terms of both the average risk (and thus R event ) and the probability distribution of secondary cases. The parameters under which well-mixed approaches are most defensible requires further evaluation, using CFD and possibly F I G U R E 1 3 Spatial particle distribution after 30 min in case of windshield defrosting ventilation mode at 50% (Q50%), breathing activity, and driver infected field investigations (e.g., tracer tests) to inform such generalizations; nonetheless, it is clear that well-mixed models can perform very well in scenarios characterized by low air exchange rates where the flow patterns are not able to provide a proper particle removal from the breathing zone of the exposed subject: this is also typical of other larger indoor environments, such as naturally-ventilated buildings, 32 where well-mixed models were shown to predict the attack rates of documented SARS-CoV-2 outbreaks. 21,27 We note the solutions here reported are very specific of the car cabin under investigation and of the boundary conditions set, as an example, we have not considered: (i) the effect of mitigation solutions, such as vaccination and face masks, 21 that could reduce the individual risk of infection of passengers, (ii) the presence of a possible fifth passenger sitting in the middle of the rear row typical of five-seater cars (please consider that his/her exposure could be different from the other passengers sitting on the rear seats due to limited shielding effect of the front seats), (iii) the effect of side window opening, (iv) the effect of the journey duration.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, several theoretical and numerical studies have demonstrated that the droplet and pollutant concentrations as well as the risk of infection are affected by the distance from the source only in the close proximity of the source, which was evaluated roughly equal to 1.5 m ( Cortellessa et al, 2021 , Chen et al, 2020 , Li, 2021 ). Beyond that distance the concentration/risk can be considered homogeneously distributed at least for distances higher than those characteristics of the investigated ward ( Lakey et al, 2021 ). In the case of initial concentration equal to 0, the indoor SARS-CoV-2 concentration can be estimated as: …”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18] A study of temporal and spatial scales suggests that chemical compounds as well as particles in the range of 1-10 µm with persistent residence time exhibit spatial gradients that are signi cantly controlled by ventilation rates. 19 Additionally, controlled experiments on participants who were diagnosed with COVID-19 were used to study the abundance of SARS-CoV-2 viral RNA copies in room aerosols. The authors found that the near-eld was associated with a higher number of virus RNA copies, and statistically higher carbon dioxide (CO 2 ), and particle counts of 0.3 µm -2.5 µm than in the far-eld.…”
Section: Introductionmentioning
confidence: 99%